A mold flux for continuous casting of steel and a method for producing the same
Patent Information
- Application Number
- CN202410693638.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-05-31
AI Technical Summary
[0006]本申请提供了一种钢连铸用结晶器保护渣及其制备方法,以解决现有结晶器保护渣降低加热炉铸坯氧化烧损的性能较差的技术问题
[0023]本申请合理设计结晶器保护渣的成分和含量,通过在保护渣中配入磷酸盐后,浇铸过程中在铸坯表面形成一层致密、耐高温的磷酸铝保护膜,铸坯加热过程中阻止氧气和铸坯表面发生反应,有效减少了铸坯烧损量,提高了金属收得率。
Smart Images

Figure CN118455471B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of steel production technology, and in particular to a mold flux for continuous steel casting and its preparation method. Background Technology
[0002] Before rolling, the billet is heated in a furnace for several hours at a temperature close to 1300℃. This prolonged high-temperature heating results in severe surface oxidation, producing a thick layer of iron oxide scale and significant oxidation loss, leading to steel wastage.
[0003] Applying anodizing coatings can effectively solve the oxidation problem during the high-temperature heating of cast billets. The coating is applied to the surface of the steel billet, and during gradual heating, forms a strong oxide isolation layer that adheres tightly to the billet surface, isolating it from the oxidizing atmosphere and effectively mitigating oxidation and burn-off. Chinese Patent CN110452565B discloses a high-temperature resistant oxidation-resistant coating for hot rolling of nickel-based alloys and its preparation method. This coating can be applied to the surface protection process during the pre-rolling heating and heat treatment of nickel-based alloys, obtaining a uniform, dense, and robust protective coating. This coating can significantly improve the oxidation and decarburization problems during the heat treatment of steel, thereby reducing the technical difficulty of hot rolling of nickel-based alloys and increasing the yield of steel. Chinese Patent CN1095391A discloses a pretreatment-free high-temperature oxidation-resistant coating, made of inorganic oxides, combined with insoluble fillers and antioxidants. Using water as a solvent, it cures at room temperature and requires no surface pretreatment for non-deeply oxidized steel. It exhibits good thermal conductivity and stability, with an operating temperature range of 800℃~1300℃ and a maximum temperature resistance of 1500℃. It effectively prevents oxidation burn-off, decarburization, and steel sticking accidents in carbon steel and alloy steel, improving the operating rate of heating furnaces and rolling mills. Chinese patent CN113025094A discloses an anti-oxidation red mud-doped coating for high-temperature steel billets. This coating is composed of red mud, silica, carboxymethyl cellulose, alumina, magnesium oxide, graphite powder, sodium silicate, and water. This invention enhances the utilization value of red mud, increases the amount of red mud waste that can be processed, and reduces the environmental impact of red mud. After being brushed onto the steel billet, it does not powder or crack under high-temperature conditions, forming a dense protective film on the billet surface, providing excellent anti-oxidation performance during heating and heat preservation.
[0004] However, most domestic hot-rolled strip steel mills employ hot-feeding and hot-charging processes, in which heat preservation is a crucial step. Typically, heat preservation pits are used as insulation equipment. Before the slab is fed into the heating furnace, it is preheated in the pits to reduce heating time in the low-temperature section of the furnace, saving costs. However, the coating process is complex and affects the hot-feeding and hot-charging temperature. Furthermore, anti-oxidation coatings are expensive to prepare and have complex application processes, limiting their use to certain special steel grades and preventing large-scale application. During hot rolling, high-pressure water cannot completely remove the coating from the slab surface, and residual coatings affect the surface quality of the steel.
[0005] Currently, there is considerable research on mold fluxes. These fluxes solidify uniformly on the surface of the cast billet during continuous casting, effectively preventing oxidation and burn-off of carbon steel and alloy steel during furnace heating. They also save spraying time, improve production efficiency, and do not affect the hot charging and hot delivery process. However, existing mold fluxes have poor performance in reducing oxidation and burn-off of cast billets in the furnace. Therefore, to address the problems existing in the current process, there is an urgent need to develop a mold flux that can effectively reduce oxidation and burn-off of cast billets in the furnace. Summary of the Invention
[0006] This application provides a mold flux for continuous casting of steel and its preparation method to solve the technical problem that existing mold fluxes have poor performance in reducing the oxidation loss of billets in heating furnaces.
[0007] In a first aspect, this application provides a mold flux for continuous casting of steel, characterized in that the chemical composition of the mold flux includes: CaO, SiO2, Al2O3, Na2O, MgO, Li2O, C, phosphates, and fluorides; wherein, by mass fraction,
[0008] The content of CaO is 30%–40%, SiO2 is 25%–35%, Al2O3 is 2%–5%, Na2O is 5%–8%, MgO is 5%–8%, Li2O is 1%–3%, C is 3%–6%, phosphate is 5%–10%, and fluoride is 3%–8%.
[0009] Optionally, the phosphate is aluminum dihydrogen phosphate.
[0010] Optionally, the fluoride is calcium fluoride.
[0011] Optionally, the crystallizer protective slag meets at least one of the following properties: basicity of 1.0 to 1.50, melting point of 1050℃ to 1200℃, and viscosity of 0.1 Pa·s to 0.5 Pa·s at 1300℃.
[0012] Secondly, this application provides a method for preparing the crystallizer protective slag according to any embodiment of the first aspect, the method comprising:
[0013] Limestone, dolomite, wollastonite, bauxite, sodium carbonate, fluorite, and lithium carbonate are mixed, heated until melted, and kept at that temperature to obtain a molten mixture.
[0014] The molten mixture is sequentially subjected to water quenching, crushing and screening, and mixing with water to obtain a slurry;
[0015] The slurry is dried, dehydrated, and granulated to obtain a pre-melted water-quenched slag; and,
[0016] The pre-melted water-quenched slag, carbonaceous materials, and phosphates are mixed to obtain a mold protective slag for continuous steel casting.
[0017] Optionally, the heating temperature is 1400℃~1500℃.
[0018] Optionally, the heat preservation time is 20 min to 50 min.
[0019] Optionally, the particle size of the granulation is 0.1 mm to 2 mm; and / or, after drying and dehydration, the mass fraction of moisture is 0.1% to 0.3%.
[0020] Thirdly, this application provides a protective film to reduce the oxidation and burning loss of the cast billet in a heating furnace, the protective film being formed by solidification of the mold flux as described in any embodiment of the first aspect.
[0021] Optionally, the protective film contains a gel-like polymer with a cross-linked network structure of phosphorus, oxygen, and aluminum.
[0022] The technical solutions provided in this application have the following advantages compared with the prior art:
[0023] This application rationally designs the composition and content of the mold flux. By adding phosphate to the flux, a dense and high-temperature resistant aluminum phosphate protective film is formed on the surface of the billet during the casting process. This prevents oxygen from reacting with the billet surface during the billet heating process, effectively reducing the amount of billet burn-off and improving the metal yield. Attached Figure Description
[0024] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0025] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 A schematic flowchart illustrating a method for preparing mold flux for continuous casting of steel, provided in an embodiment of this application;
[0027] Figure 2 The diagram shows the thickness of the iron oxide scale after heating in the furnace for casting Q345R mold flux as provided in Embodiment 1 of this application.
[0028] Figure 3 The diagram shows the thickness of the iron oxide scale after heating in the furnace for casting Q345R mold flux as provided in Embodiment 2 of this application.
[0029] Figure 4 The diagram shows the thickness of the iron oxide scale after heating in the furnace, provided in Comparative Example 1 of this application, for casting Q345R mold flux for the crystallizer. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0031] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.
[0032] Furthermore, in the description of this application, the terms "comprising," "including," etc., mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.
[0033] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0034] In a first aspect, this application provides a mold flux for continuous casting of steel, characterized in that the chemical composition of the mold flux includes: CaO, SiO2, Al2O3, Na2O, MgO, Li2O, C, phosphates, and fluorides; wherein, by mass fraction,
[0035] The content of CaO is 30%–40%, SiO2 is 25%–35%, Al2O3 is 2%–5%, Na2O is 5%–8%, MgO is 5%–8%, Li2O is 1%–3%, C is 3%–6%, phosphate is 5%–10%, and fluoride is 3%–8%.
[0036] In some implementations, controlling the CaO content to 30%–40% has the following positive effects: increasing the CaO content in the protective slag increases its basicity, significantly reduces its viscosity, and enhances its ability to absorb oxide inclusions in the steel. High-basicity protective slag can increase the rate of dissolving and absorbing inclusions in steel; however, the viscosity of basic slag varies considerably with temperature. When cooled to the liquidus temperature, due to its strong crystallization ability, crystals continuously precipitate, severely damaging the glassiness of the slag and causing defects in the cast billet. The CaO content can be 30%, 32%, 35%, 37%, 40%, etc.
[0037] The positive effects of controlling the SiO2 content to 25%–35% are: Higher SiO2 content in the protective slag increases its glassiness, ensuring smooth continuous casting. However, excessively high SiO2 content, while improving the lubrication ability of the protective slag, is detrimental to the formation of anti-oxidation slag in the later stages of continuous casting. Therefore, the SiO2 content in this invention is slightly lower than that of traditional slags. The SiO2 content can be 25%, 28%, 30%, 32%, 35%, etc.
[0038] The positive effects of controlling the Al2O3 content to 2%–5% are as follows: Excessive Al2O3 addition will worsen the lubrication of the slag and increase its viscosity, while appropriate addition can lower the solidification point of the protective slag, thereby improving its lubrication. The Al2O3 content can be 2%, 3%, 4%, 5%, etc.
[0039] The positive effects of controlling the Na₂O content to 5%–8% are as follows: Na₂O is a network exooxide that can disrupt the silicate structure, mainly playing a role in lowering the melting temperature and improving the fluidity of the protective slag. The Na₂O content can be 5%, 6%, 7%, 8%, etc.
[0040] The positive effects of controlling the MgO content to 5%–8% are as follows: MgO replaces some CaO in the protective slag, inhibiting crystal precipitation in the high-temperature range, reducing the interfacial tension between the slag and inclusions, and facilitating the wetting of inclusions by the slag. As its mass fraction increases, the melting temperature of the continuous casting protective slag decreases significantly. However, excessively high content can easily lead to the formation of high-melting-point crystalline mineral phases. The MgO content can be 5%, 6%, 7%, 8%, etc.
[0041] The positive effects of controlling the Li₂O content to 1%–3% include: Li₂O can reduce viscosity and melting temperature. The Li₂O content can be 1%, 2%, 3%, etc.
[0042] The positive effects of controlling the carbon content to 3%–6% include: carbonaceous materials such as carbon black and coke powder act as melting rate regulators to adjust the melting structure and melting speed of the protective slag; appropriate addition can yield sintered layers and liquid slag layers of suitable thickness. The carbon content can be 3%, 4%, 5%, 6%, etc.
[0043] The positive effects of controlling the phosphate content to 5%–10% include: Phosphate acts as a binder for the antioxidant protective slag. As a binder for the heat insulation film, it exhibits strong adhesion, directly affecting many properties of the cast billet coating. The antioxidant protective slag uses high-temperature resistant aluminum phosphate binder as the film-forming material, demonstrating excellent high-temperature stability and oxidation resistance. The phosphate content can be 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0044] The positive effects of controlling the fluoride content to 3%–8%: Fluorides are added to the protective slag in the form of CaF2, which acts as a flux. Fluorides play a crucial role in regulating the high-temperature properties of the protective slag, primarily lowering the melting temperature and improving its fluidity. An appropriate amount of fluoride ions in the molten slag can promote the disintegration of silicon-oxygen polymers, resulting in better heat transfer in the slag film. The fluoride content can be 3%, 4%, 6%, 7%, or 8%, etc.
[0045] In some embodiments, the phosphate is aluminum dihydrogen phosphate.
[0046] Through optimization, aluminum dihydrogen phosphate was added to the protective slag in this application. During high-temperature heating, aluminum dihydrogen phosphate first forms aluminum tripolyphosphate, and as the temperature continues to rise, it transforms into aluminum metaphosphate and aluminum pyrophosphate, etc., to obtain a colloidal polymer with a cross-linked network structure of phosphorus, oxygen, and aluminum.
[0047] In some embodiments, the fluoride is calcium fluoride.
[0048] The technical principle of the mold flux composition formulation for the continuous casting process in this application is as follows:
[0049] According to the theory of non-isothermal reaction kinetics, the kinetic equation for the decomposition reaction of solid substances under linear heating conditions is:
[0050] βdα / dT=A·e -E / (RT) f(α)
[0051] In the formula, β represents the linear heating rate (℃ / min), α represents the reaction decomposition fraction at temperature T (K), A is the frequency factor (min-1), E is the activation energy (J / mol), and f(α) represents the kinetic mechanism function.
[0052] The non-isothermal kinetics of solid-phase decomposition reactions were studied using the Doyle mechanism equation:
[0053]
[0054] In the formula,
[0055] Based on the above non-isothermal reaction kinetics theory, it can be determined that the thermal decomposition of aluminum dihydrogen phosphate during continuous heating mainly consists of four stages, and the reaction equations for the four stages are as follows:
[0056] (H₂PO₄)₃→amor.PO₄+H₂
[0057] H2P3O 10 2.5H₂O → 2P₆O 18 +3.5H2
[0058] 2P6O 18 →(PO3)3
[0059] 6(PO3)3→6PO4+15O2↑
[0060] The final reaction product is Al(PO3)3 with high viscosity, which adheres to the surface of the billet and then transforms into high-temperature resistant AlPO4 in the high-temperature region. During the heating process of the billet, it can prevent the billet from continuing to oxidize and play an antioxidant role.
[0061] In some embodiments, the crystallizer protective slag satisfies at least one of the following properties: basicity of 1.0 to 1.50, melting point of 1050°C to 1200°C, and viscosity of 0.1 Pa·s to 0.5 Pa·s at 1300°C.
[0062] The positive effects of controlling the basicity to 1.0–1.50: Changes in the basicity of the protective slag typically alter the viscosity of the molten protective slag, thereby indirectly affecting its crystallization temperature. If the basicity is too high, the viscosity of the protective slag decreases, leading to a drop in its crystallization temperature. This basicity can be 1.0, 1.1, 1.3, 1.4, 1.5, etc.
[0063] The positive effects of controlling the melting point to 1050℃~1200℃: In the continuous casting process, the melting temperature of the protective slag directly affects the thickness of the molten slag layer on the surface of the molten steel in the mold and the thickness of the slag film between the mold and the billet shell, thus affecting the surface quality of the billet shell, the amount of protective slag flowing between the mold and the billet shell, and the amount of protective slag consumed. As the slag melting temperature decreases, the consumption of protective slag increases; therefore, controlling the melting point of the protective slag to 1050℃~1200℃ is crucial. This melting point can be 1050℃, 1080℃, 1120℃, 1160℃, 1200℃, etc.
[0064] The positive effects of controlling the viscosity at 1300℃ to 0.1 Pa·s~0.5 Pa·s: The viscosity of the protective slag is an important indicator of its lubricity and is closely related to its melting behavior on the meniscus. It has a significant impact on the surface quality of the cast billet. During casting, the protective slag can ensure a certain thickness and uniform spread of the slag film, thereby improving the lubrication and stabilizing heat transfer of the cast billet. Viscosity affects the thickness and uniformity of the slag film. If the viscosity is too low, the slag film formed between the mold and the billet shell will be thick and uneven, leading to uneven heat transfer and uneven solidification of the cast billet, causing cracks. If the viscosity is too high, the slag flow will be obstructed across the meniscus, the slag film will be thin, the slag fluidity will be poor, and lubrication will be inadequate. In addition, excessively high viscosity protective slag is prone to forming slag streaks, resulting in low slag consumption and uneven slag film thickness, which increases the heat flux density of the mold, leading to longitudinal cracks in the cast billet or even sticking and leakage. The viscosity can be 0.1 Pa·s, 0.2 Pa·s, 0.3 Pa·s, 0.4 Pa·s, 0.5 Pa·s, etc.
[0065] Secondly, this application provides a method for preparing a mold flux for continuous casting of steel, the method being used to prepare the mold flux described in any embodiment of the first aspect, the method comprising:
[0066] S1. Mix limestone, dolomite, wollastonite, bauxite, sodium carbonate, fluorite and lithium carbonate, then heat until melted and keep warm to obtain a molten mixture;
[0067] In the embodiments of this application, limestone, dolomite, wollastonite, bauxite, sodium carbonate, fluorite, lithium carbonate, carbonaceous materials, and phosphates are used as raw materials, and each raw material meets the following requirements: CaCO3 > 95% in limestone, CaO > 44% and SiO2 > 47% in wollastonite, Al2O3 > 75% in bauxite, CaCO3 > 50% and MgCO3 > 40% in dolomite, Na2CO3 > 95% in sodium carbonate, CaF2 > 88% and S < 0.05% in fluorite, and C > 95% in carbonaceous materials.
[0068] In some embodiments, the heating temperature is 1400°C to 1500°C.
[0069] The positive effects of controlling the heating temperature to 1400℃~1500℃ are as follows: Within this temperature range, the raw materials melt, and limestone decomposes into CaO, wollastonite into CaO and SiO2, dolomite into CaO and MgO, and Na2CO3 into Na2O. This heating temperature can be 1400℃, 1420℃, 1450℃, 1470℃, 1500℃, etc.
[0070] In some embodiments, the heat preservation time is 20 to 50 minutes. The heat preservation time can be 20 minutes, 30 minutes, 40 minutes, 50 minutes, etc.
[0071] S2. The molten mixture is sequentially quenched with water, crushed and screened, and then mixed with water to obtain a slurry;
[0072] S3. The slurry is dried, dehydrated, and granulated to obtain pre-melted water-quenched slag;
[0073] In some embodiments, the particle size of the granulation is 0.1 mm to 2 mm; and / or, after drying and dehydration, the mass fraction of moisture is 0.1% to 0.3%.
[0074] The particle size of this granulation can be 0.1mm, 0.5mm, 1.0mm, 1.5mm, 2mm, etc.; after drying and dehydration, the mass fraction of the moisture can be 0.1%, 0.2%, 0.3%, etc.
[0075] S4. Mix the pre-melted water-quenched slag, carbonaceous material and phosphate to obtain a mold protective slag for continuous steel casting.
[0076] Thirdly, this application provides a protective film to reduce the oxidation and burning loss of the cast billet in a heating furnace, the protective film being formed by solidification of the mold flux as described in any embodiment of the first aspect.
[0077] In some embodiments, the protective film contains a gel-like polymer with a cross-linked network structure of phosphorus, oxygen, and aluminum.
[0078] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0079] Example 1
[0080] The raw materials used in this embodiment are dolomite, wollastonite, bauxite, sodium carbonate, fluorite, lithium carbonate, coke powder, and aluminum dihydrogen phosphate.
[0081] The preparation method of the protective slag in this embodiment consists of the following preparation steps:
[0082] Weigh out 31.5 kg of dolomite, 58.4 kg of wollastonite, 4.7 kg of bauxite, 13.4 kg of sodium carbonate, 7.2 kg of fluorite, and 3.2 kg of lithium carbonate, crush and mix them, heat to 1400℃ to melt, and then hold at that temperature for 30 minutes to obtain a molten mixture. Pour the molten mixture into water at approximately 20℃ for cooling to obtain a glassy protective slag, crush it to 200 mesh, and mix it to form a slurry. Dry the resulting slurry, controlling the moisture content to 0.12%, and finally granulate it to control the particle size to 1.5 mm. Mix the pre-prepared carbonaceous materials, phosphates, and pre-melted water-quenched slag evenly to produce a protective slag that resists billet oxidation in the heating furnace.
[0083] Example 2
[0084] The raw materials selected for preparation in this embodiment are limestone, dolomite, wollastonite, bauxite, sodium carbonate, fluorite, lithium carbonate, coke powder, and aluminum dihydrogen phosphate.
[0085] The preparation method of the protective slag in this embodiment consists of the following preparation steps:
[0086] Weigh out 4 kg of limestone, 28.5 kg of dolomite, 61.8 kg of wollastonite, 4.5 kg of bauxite, 11.9 kg of sodium carbonate, 6.7 kg of fluorite, and 3.8 kg of lithium carbonate, crush and mix them, heat to 1430℃ to melt, and then hold at that temperature for 25 minutes to obtain a molten mixture. Pour the molten mixture into water at approximately 20℃ for cooling to obtain a glassy protective slag, crush it to 200 mesh, and mix it to form a slurry. Dry the resulting slurry, controlling the moisture content to 0.14%, and finally granulate it to control the particle size to 1.5 mm. Mix the pre-prepared carbonaceous materials, phosphates, and pre-melted water-quenched slag evenly to produce a protective slag that resists billet oxidation in the heating furnace.
[0087] Comparative Example 1
[0088] The raw materials used in this comparative example were limestone, dolomite, wollastonite, bauxite, sodium carbonate, fluorite, lithium carbonate, and coke powder.
[0089] The preparation method of the comparative protective slag consists of the following steps:
[0090] Weigh out 8 kg of limestone, 25.1 kg of dolomite, 63.4 kg of wollastonite, 4.5 kg of bauxite, 10.2 kg of sodium carbonate, 6.6 kg of fluorite, and 3.9 kg of lithium carbonate, crush and mix them, heat to 1480℃ to melt, and then hold at that temperature for 25 minutes to obtain a molten mixture. Pour the molten mixture into water at approximately 20℃ for cooling to obtain a glassy protective slag, crush it to 200 mesh, and mix it to form a slurry. Dry the resulting slurry, controlling the moisture content to 0.12%, and finally granulate it to control the particle size to 1.5 mm. Mix the pre-prepared carbonaceous materials and pre-melted water-quenched slag evenly to prepare a comparative protective slag.
[0091] The composition and mass fraction of the protective slag prepared according to the methods of Examples 1, 2 and Comparative Example 1 are shown in Table 1.
[0092] Table 1. Composition and mass fraction (wt%) of protective slag
[0093]
[0094] The melting point of the protective slags prepared by the methods of Examples 1, 2 and Comparative Example 1 was tested using a melting point and melting rate tester (hemispherical method); the viscosity of the protective slags prepared by the methods of Examples 1, 2 and Comparative Example 1 was tested using a high-temperature melt property analyzer (rotating cylinder method). The performance results are shown in Table 2.
[0095] Table 2 Performance results of protective slag
[0096]
[0097] The protective slags prepared by the methods of Examples 1, 2 and Comparative Example 1 were cast into Q345R and then heated in a furnace at 1250°C for 4 hours. The thickness of the iron oxide scale in different parts of the cast billet after heating is shown in Table 3.
[0098] Table 3. Iron oxide scale thickness at different parts of the Q345R billet after heating when using protective slag casting.
[0099]
[0100] From Table 3 and Appendix Figure 2-4 It is evident that by adding phosphate to the protective slag, the resulting iron oxide scale is thinner, and the problem of significant oxidation and burn-off is greatly reduced, playing a significant role in the continuous casting process of steel.
[0101] Furthermore, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0102] In this embodiment of the invention, during the solidification process of the continuously cast billet shell, the protective slag is uniformly solidified on the surface of the billet. During the heating process in the heating furnace, it can effectively prevent the oxidation and burning of carbon steel and alloy steel, save spraying time, improve production efficiency, and has no impact on the hot charging and hot delivery process.
[0103] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A mold flux for continuous steel casting, characterized in that, The chemical composition of the crystallizer protective slag includes: CaO, SiO2, Al2O3, Na2O, MgO, Li2O, C, phosphates, and fluorides; wherein, by mass fraction, The content of CaO is 30%–40%, SiO2 is 25%–35%, Al2O3 is 2%–5%, Na2O is 5%–8%, MgO is 5%–8%, Li2O is 1%–3%, C is 3%–6%, phosphate is 5%–10%, and fluoride is 3%–8%.
2. The crystallizer protective slag according to claim 1, characterized in that, The phosphate is aluminum dihydrogen phosphate.
3. The crystallizer protective slag according to claim 1, characterized in that, The fluoride is calcium fluoride.
4. The crystallizer protective slag according to claim 1, characterized in that, The protective slag for the crystallizer meets at least one of the following properties: basicity of 1.0 to 1.50, melting point of 1050℃ to 1200℃, and viscosity of 0.1 Pa·s to 0.5 Pa·s at 1300℃.
5. A method for preparing the crystallizer protective slag according to any one of claims 1-4, characterized in that, The method includes: Limestone, dolomite, wollastonite, bauxite, sodium carbonate, fluorite, and lithium carbonate are mixed, then heated until melted and kept at that temperature to obtain a molten mixture. The molten mixture is sequentially subjected to water quenching, crushing and screening, and mixing with water to obtain a slurry; The slurry is dried, dehydrated, and granulated to obtain a pre-melted water-quenched slag; and, The pre-melted water-quenched slag, carbonaceous materials, and phosphates are mixed to obtain a mold protective slag for continuous steel casting.
6. The method according to claim 5, characterized in that, The heating temperature is 1400℃~1500℃.
7. The method according to claim 5, characterized in that, The heat preservation time is 20 min to 50 min.
8. The method according to claim 5, characterized in that, The granulation particle size is 0.1 mm to 2 mm; and / or, after drying and dehydration, the moisture content is 0.1% to 0.3% by mass.
9. A protective film for reducing oxidation loss of cast billets in a heating furnace, characterized in that, The protective film is formed by solidification of the crystallizer protective slag as described in any one of claims 1-4.
10. The protective film according to claim 9, characterized in that, The protective film contains a gel-like polymer with a cross-linked network structure of phosphorus, oxygen, and aluminum.
Citation Information
Patent Citations
Pretreatment-free high-temp. antioxidant coating
CN1095391A
A high-temperature resistant and oxidation-resistant coating for hot rolling of nickel-based alloys and its preparation method
CN110452565B
Antioxidant red mud doped coating for high-temperature steel billet
CN113025094A
Heat-preservation and flame-retardant casting covering slag
CN105478728A
Continuous casting crystallizer function protection material for 2Cr13 stainless steel and preparation method of continuous casting crystallizer function protection material
CN117900401A